2019
DOI: 10.31234/osf.io/yfn56
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct and indirect links between children’s socio-economic status and education: Pathways via mental health, attitude, and cognition

Abstract: A child’s socio-economic status has been independently associated with poorer educational outcomes, slower cognitive development, and mental ill-health. However, while these factors clearly do not operate in a vacuum, testing all within a single study is challenging, and their interrelations thus remain largely unclear. We aimed to close this knowledge gap by developing a comprehensive tablet-based assessment of developmental variables in a sample of 519 children aged 7-9 years. We employed clustering algorith… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
(69 reference statements)
2
13
0
Order By: Relevance
“…Despite different value systems, the present analysis identified similar patterns in the support networks emphasized by adolescents of different ages in both countries. First, in line with previous resilience network studies (Briganti & Linkowski, 2020; Dalmaijer et al, 2020; Fritz et al, 2018, 2019), all resource networks were characterized by mostly positive resource associations giving further evidence that resources tend to positively influence each other.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Despite different value systems, the present analysis identified similar patterns in the support networks emphasized by adolescents of different ages in both countries. First, in line with previous resilience network studies (Briganti & Linkowski, 2020; Dalmaijer et al, 2020; Fritz et al, 2018, 2019), all resource networks were characterized by mostly positive resource associations giving further evidence that resources tend to positively influence each other.…”
Section: Discussionsupporting
confidence: 83%
“…A longitudinal study with adolescents from England has shown that inter‐ and intrapersonal resilience resources are mutually dependent and that childhood adversity can lead to a dysfunctional resource network that has lasting negative effects on access to the resources needed to support mental health at 14 and 17 years of age (Fritz, Fried, Goodyer, Wilkinson, & van Harmelen, 2018; Fritz et al, 2019). Another study with 7‐ to 9‐year‐old children from England that investigated a network of socioeconomic risk factors, educational outcomes, mental health, and multiple indicators for cognitive and psychological resources showed that the negative effects of depression and anxiety on educational outcomes are indirect and moderated by cognitive resources (Dalmaijer et al, 2020). Hence, these studies give first insights into resilience being constituted by mutually dependent resources from different systems and that resource interactions can be influenced by contextual variables.…”
Section: Resource Systems During Adolescence and The Influence Of Conmentioning
confidence: 99%
“…Having said that, Dweck's research is still controversial, one major study being unable to replicate the key claims about the large effects of different types of feedback [96], and another suggesting that the effect sizes suggested by the original studies can mostly not be replicated [97]. A further study has also included measures of the growth mindset within a wide range of attitudinal, background and other measures [98] and shows the growth mindset to be highly correlated with "grit" and in particular the Big Five measure of conscientiousness, which has repeatedly been shown to correlate with academic success [73,99]. Feedback and responses to feedback may therefore be dependent on differences in personality, perhaps with students at different schools differing in personality as a result of self-selection.…”
Section: The Extent To Which Preparedness Is An Important Predictive mentioning
confidence: 99%
“…Participants’ postcodes were obtained from schools or parents to compute their income deprivation affecting children index (IDACI). We have previously demonstrated that our assessments are of good reliability and validity (14), and have described the relationships between measures elsewhere (15).…”
Section: Methodsmentioning
confidence: 84%